1996
DOI: 10.2307/3432990
|View full text |Cite
|
Sign up to set email alerts
|

Health Effects of Acid Aerosols on North American Children: Respiratory Symptoms

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. The National Institute of Environmental Health Sciences (NIEHS) andBrogan & Partners are collaborating with JSTOR to digitize, preserve and extend access to Environmental Heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
81
3
5

Year Published

2000
2000
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(97 citation statements)
references
References 9 publications
8
81
3
5
Order By: Relevance
“…In each study, exposure -effects relationships can be derived for the pollution range encountered in the study and thus, a wide pollution range is favorable. The eight districts of this study exhibited a wide range for each concerned pollutant, as shown clearly in Figure 5 where the ranges from major previous US /Europe studies are also shown for comparison purposes (Ware et al, 1986;Dockery et al, 1989Dockery et al, , 1996Spengler et al, 1996;Braun -Fahrlander et al, 1997;Peters et al, 1999b;Pikhart et al, 2000 ). The comparison indicates that the data on pollution levels collected in this study substantially extended the upper end of the pollution ranges of major published studies.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…In each study, exposure -effects relationships can be derived for the pollution range encountered in the study and thus, a wide pollution range is favorable. The eight districts of this study exhibited a wide range for each concerned pollutant, as shown clearly in Figure 5 where the ranges from major previous US /Europe studies are also shown for comparison purposes (Ware et al, 1986;Dockery et al, 1989Dockery et al, , 1996Spengler et al, 1996;Braun -Fahrlander et al, 1997;Peters et al, 1999b;Pikhart et al, 2000 ). The comparison indicates that the data on pollution levels collected in this study substantially extended the upper end of the pollution ranges of major published studies.…”
Section: Discussionsupporting
confidence: 68%
“…Health effects of exposure to ambient air pollution have been extensively investigated in epidemiological studies in North American and European cities ( Chapman et al, 1985;Ware et al, 1986;Dockery et al, 1993Dockery et al, , 1996Pope et al, 1995;Peters et al, 1999a,b;Pikhart et al, 2000 ). Although these studies have found, more or less, evidence of adverse health effects of air pollution exposure, the available results remain subject to significant uncertainties in several key areas including: (1 ) the community health effects of longterm exposure; ( 2) the relative health importance of different air pollutants and different size fractions and constituents of atmospheric particles; (3 ) the ethnic, demographic, and other factors that influence susceptibility to air pollution effects.…”
Section: Introductionmentioning
confidence: 99%
“…The strong negative association between hydrogen ion and ED visits was surprising given that relatively high peak levels were observed, although results from epidemiologic studies of the effects of hydrogen ion have been mixed. Significant positive associations with various adverse health outcomes have been reported by some investigators (Burnett et al, 1997a;Delfino et al, 1997;Dockery et al, 1996a;Lippmann and Ito, 1995;Neas et al, 1995;Raizenne et al, 1996;Thurston et al, 1994 ), whereas in other studies, no effect was apparent (Dockery et al, 1996b;Schwartz et al, 1996) , or the effect of hydrogen ion was weaker than that of other measures of particulate matter (Dockery et al, 1993 ). This could be partially mediated by a very weak correlation between levels measured at centrally located monitors and personal exposure, which we have observed in Saint John (Stieb et al, 1998b) , and which has been reported elsewhere (Brauer et al, 1989;Suh et al, 1992 ).…”
Section: Discussionmentioning
confidence: 94%
“…As a result, four studies distinguished exposure groups by areas with different measured pollutant levels (Ware et al, 1986;Dockery et al, 1989;Pope, 1991;Horstman et al, 1997 ). In four other studies, exposure groups were aggregated from populations of different areas with comparable pollutant levels (Schenker et al, 1983(Schenker et al, ,1986Dockery et al, 1996;Raizenne et al, 1996 ). Table 2 summarizes the study populations, the numbers and types of exposed and control groups, and the scale of study areas.…”
Section: Study Characterizationmentioning
confidence: 99%